Covid 19 Impact on Food Crop Agriculture in East Java Indonesia - Nugrahini Susantinah Wisnujati; Endang Noerhartati (LPPM of NAROTAMA UNIVERSITY, 2020)
Agriculture in Indonesia, one of which is food crop agriculture, food crops are dominated by rice and corn products. Indonesia, which was previously known as the most significant food-producing country in the world, is currently experiencing a shift, where Indonesia's rice production has decreased compared to China. The condition of Indonesia's rice and corn production in the world will have an impact on the status of rice and corn in Indonesia, especially in East Java, East Java is a region that has the potential to produce rice and corn compared to the other area in Indonesia, on the other hand, because of Indonesia's demand for rice and corn large enough. The occurrence of COVID 19 has an impact on all aspects of the world and all sectors, one of which is food crops, how the effects of COVID 19 on food crop agriculture in East Java, the results of the study are the behavior of farmers in East Java relatively no difference before the occurrence of COVID 19 and after COVID 19, farmers still work as usual. Rice supply at the level of the farmer community is still sufficient because farmers have harvested a month in March 2020. In Bangkalan Madura the village government has the policy to carry out the harvest by renting harvest tools to anticipate COVID 19, while in Gresik and Lamongan areas farmers continue to do the harvest without assistance harvester. The role of advisory counselors is needed by farmers, this is because extension agents can become counselors of the COVID 19 problem in the community during a pandemic like this, and this is in line with research (Adawiyah, Sumardjo, and Mulyani 2018) that farmers' facilitators influence the adoption of new technologies. With the COVID 19 outbreak, the brothers of the farmers returned home because of the culture of going back or also because the factories, shops, restaurants where they work have been close, this is a burden for farmers.